2017
DOI: 10.29313/mimbar.v33i1.2029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Accounting Information Quality, Accountability, and Transparency on Zakat Acceptance

Abstract: Abstract. This study aims to prove the effects of accounting information quality, accountability, and transparency on the acceptance of zakat. The population of this research is Zakat Collection Agency (LAZ) in Semarang City, Central Java province. The samples are taken by using purposive sampling. They are Zakat Collection Agency in Semarang that have the largest zakat revenue source and the widest distribution. The research samples taken include: BAZNAS Semarang, LAZISBA Baiturrahman Masjid, DPU Daarut Tauhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 1 publication
0
9
1
6
Order By: Relevance
“…This finding indicates that a zakat collection institution's accountability is not used as a factor used by muzakki in building image, building trust, and even in generating motivation to pay zakat through a collection institution. This finding is different from the findings of Mutmainah (2015); Nikmatuniayah et al (2017); and Pangestu & Jayanto (2017) who find that accountability has a significant influence on the intention to pay zakat. According to the results of this study, there are indications that muzakki pay zakat through collection institutions and muzakki have a tendency to ignore the accountability of those institutions to muzakki.…”
Section: Share | Volume 8 | Number 1 | Jan -Jun 2019contrasting
confidence: 93%
See 1 more Smart Citation
“…This finding indicates that a zakat collection institution's accountability is not used as a factor used by muzakki in building image, building trust, and even in generating motivation to pay zakat through a collection institution. This finding is different from the findings of Mutmainah (2015); Nikmatuniayah et al (2017); and Pangestu & Jayanto (2017) who find that accountability has a significant influence on the intention to pay zakat. According to the results of this study, there are indications that muzakki pay zakat through collection institutions and muzakki have a tendency to ignore the accountability of those institutions to muzakki.…”
Section: Share | Volume 8 | Number 1 | Jan -Jun 2019contrasting
confidence: 93%
“…Indeed, a low level of ransparency is the cause of low levels of zakat payment (Nugraha, Wardayati, & Sayekti, 2018). Mutmainah (2015) ;Nikmatuniayah, et al (2017); dan Pangestu & Jayanto (2017) have demonstrated empirically that transparency in zakat collection institutions has a positive influence on the strength of the intention of muzakki to make zakat payments. On the basis of these existing theories, the fourth hypothesis is proposed as below: H4: Transparency in zakat collection institutions has a positive influence on interest in paying zakat.…”
Section: Theoretical Basis and Hypothesis Developmentmentioning
confidence: 99%
“…Because it has significant effect, it means that financial accountability is necessary for zakat management institutions. A study by Nikmatuniayah, Marliyati, and Mardiana A (2017) shows that accountability has positive influence on level of acceptance of zakat fund. PSAK 109 already regulates the disclosure (accountability) which must be done by LAZ.…”
Section: Resultsmentioning
confidence: 99%
“…According to Foster (2001), the length of time a person has taken makes him more aware of his duties and position in the organization than members who have already joined. 25.00. It can be concluded that if the mean value is 25.10 > 25.00 of median value, the variable of organizational commitment is said to be high.…”
Section: Resultsmentioning
confidence: 99%